Detection of influenza A(H3N2) viruses exhibiting reduced susceptibility to the novel cap-dependent endonuclease inhibitor baloxavir in Japan, December 2018 - Takashita, Emi; Kawakami, Chiharu; Morita, Hiroko; Ogawa, Rie; Fujisaki, Seiichiro; Shirakura, Masayuki; Miura, Hideka; Nakamura, Kazuya; Kishida, Noriko; Kuwahara, Tomoko; Mitamura, Keiko; Abe, Takashi; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2019)
The novel cap-dependent endonuclease inhibitor baloxavir marboxil was approved for the treatment of influenza virus infection in Japan in February 2018. Two influenza A(H3N2) viruses carrying an I38T substitution in the polymerase acidic subunit (PA) were detected in baloxavir-treated children in December 2018. This mutation is known to confer reduced susceptibility to baloxavir, and the two mutant viruses exhibited 76- and 120-fold reduced susceptibility to baloxavir.